PROGNOSTIC VALUE OF IMMUNOLOGICAL AND GENETIC TESTING IN THE I TRIMESTER OF PREGNANCY COMPLICATED BY SUBCHORIONIC HEMATOMA - M. V. Utrobin; S. V. Yur’ev (Опухоли женской репродуктивной системы)
Introduction. Pregravid preparation plays a main role in solving issues with recurrent miscarriage and preterm delivery. Detection of etiologic factors of miscarriage with development of preventive strategies seems reasonable.Study objective was to optimize the assessment and treatment algorithms of threatening miscarriage in the I  trimester of pregnancy with subchorionic hematoma formation.Materials and methods. 113 women with subchorionic hematoma were examined in gestational age 4 to 12 weeks. Monitoring of pregnancy till delivery was conducted.Results. The role of the combination of coagulation system genes polymorphisms (II  and V coagulation factors, plasminogen activator inhibitor-1,  methylenetetrahydrofolatereductase) and  altered  level  of  autoantibodies against thyroglobulin in  increased probability of miscarriage was shown.Conclusion. Identification of high risk patients for pregnancy loss in the first trimester by the combination of coagulation system genes polymorphisms and antibody marker of thyroiditis together with a personified therapy approach contribute to the prolongation of pregnancy and reduce the frequency of repeated miscarriage.